2017
DOI: 10.1097/yic.0000000000000180
|View full text |Cite
|
Sign up to set email alerts
|

Effects of vilazodone on suicidal ideation and behavior in adults with major depressive disorder or generalized anxiety disorder

Abstract: Treatment-emergent suicidal ideation and behavior are ongoing concerns with antidepressants. Vilazodone, currently approved for the treatment of major depressive disorder (MDD) in adults, has also been evaluated in generalized anxiety disorder (GAD). Post-hoc analyses of vilazodone trials were carried out to examine its effects on suicidal ideation and behavior in adults with MDD or GAD. Data were pooled from vilazodone trials in MDD (four studies) and GAD (three studies). The incidence of suicide-related even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
(43 reference statements)
1
2
0
Order By: Relevance
“…Pooled data for clinical trials of GAD and MDD showed that the incidences of suicidal ideation and behavior based on C-SSRS were similar or lower than placebo for vilazodone, a combined reuptake inhibitor and a 5-HT 1A receptor partial agonist approved for MDD in 2011. 46 The aforementioned studies agree with the meta-analyses of 207 randomized controlled trials of antidepressants and suicide-related events evaluated by the FDA. 14 Taken together, independent FDA analyses and data from various clinical trials suggest the safety of antidepressants and low risk of suicidal behavior in MDD patients taking antidepressants.…”
Section: Discussionsupporting
confidence: 79%
“…Pooled data for clinical trials of GAD and MDD showed that the incidences of suicidal ideation and behavior based on C-SSRS were similar or lower than placebo for vilazodone, a combined reuptake inhibitor and a 5-HT 1A receptor partial agonist approved for MDD in 2011. 46 The aforementioned studies agree with the meta-analyses of 207 randomized controlled trials of antidepressants and suicide-related events evaluated by the FDA. 14 Taken together, independent FDA analyses and data from various clinical trials suggest the safety of antidepressants and low risk of suicidal behavior in MDD patients taking antidepressants.…”
Section: Discussionsupporting
confidence: 79%
“…A pooled analysis of data from 8 clinical studies focused on the effects of vilazodone on measures of suicidal ideation, including treatment-emergent suicidality. 55 Among patients with suicidal ideation at baseline, a higher proportion of vilazodone-treated patients reported resolution of suicidal ideation during double-blind treatment than subjects who received placebo (39% to 45% vs 29% to 33%). Rates of treatment-emergent suicidal behaviors (eg, preparatory acts, aborted/interrupted attempts, attempted suicide) were similar between vilazodone and placebo (0.3–0.8% vs 0.1–0.7%).…”
Section: Clinical Efficacymentioning
confidence: 99%
“…For example, a megaanalysis of adults receiving citalopram, paroxetine, sertraline, or placebo for major depression there was a significant decrease in the mean rating of suicidality on the Hamilton Rating Scale for Depression (HRSD) in subjects over 25 years old (Näslund et al, 2018). Numerous other studies also found reduction in suicidality, measured by varying rating scales, versus placebo or tricyclic antidepressants among adults taking SRIs (Beasley et al, 1991;Grunebaum et al, 2012;Gunnell et al, 2005;Hawton et al, 2015;Isacsson et al, 2009;Khan et al, 2018;Thase et al, 2017).…”
Section: Antidepressantsmentioning
confidence: 99%